2014
DOI: 10.1016/j.jcyt.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of N-acetylcysteine and Liberase improves the viability and metabolic function of human hepatocytes isolated from human liver

Abstract: Background aimsSuccessful hepatocyte isolation is critical for continued development of cellular transplantation. However, most tissue available for research is from diseased liver, and the results of hepatocyte isolation from such tissue are inferior compared with normal tissue. Liberase and N-acetylcysteine (NAC) have been shown separately to improve viability of isolated hepatocytes. This study aims to determine the effect of Liberase and NAC in combination on human hepatocyte isolation from normal and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Some studies have also found that NAC increased the level of glutathione in human hepatocytes, which may be responsible for the hepatocyte‐protective effects. Recently, NAC has been introduced for use in hepatocyte isolation . In the present experiment, administration of NAC in reperfusion largely ameliorated cell damage, as shown by reduced ALT and AST.…”
Section: Discussionsupporting
confidence: 50%
“…Some studies have also found that NAC increased the level of glutathione in human hepatocytes, which may be responsible for the hepatocyte‐protective effects. Recently, NAC has been introduced for use in hepatocyte isolation . In the present experiment, administration of NAC in reperfusion largely ameliorated cell damage, as shown by reduced ALT and AST.…”
Section: Discussionsupporting
confidence: 50%
“…With upgrade of commercial collagenase products such as Roche Liberase research grades and Serva collagenase NB grades, the isolations are more specific to the species, while the purity, viability, and yield of isolated primary hepatocytes are highly improved [4,18]. Except for the primary component, highly purified collagenaseand Ⅱmixture, we found that the amount of neutral protease thermolysin also determines the viability and cell yield, and especially the further success of spheroid formation.…”
Section: Hepatocyte Isolationmentioning
confidence: 87%
“…It also has direct antioxidant properties and appears to have hepatoprotective effects against liver ischemia/reperfusion injury to improve the viability [9]. It has been proved to improve the viability and conserves the metabolic function of hepatocytes [4,18].…”
Section: Hepatocyte Isolationmentioning
confidence: 99%
“…Recent introduction of liberase, an enzyme used in pancreatic islet cell isolation, and N -acetylcysteine (NAC), an antioxidant with multiple hepatoprotective properties, into established isolation protocols has enabled improvements in overall isolation success from 40% to 70% (33, 50, 51). Additional strategies such as machine perfusion techniques and perfusate selection have been shown to dramatically increase cell yields (52, 53).…”
Section: Improving Human Hepatocytes Qualitymentioning
confidence: 99%